“Good Mothers” Breastfeed: Discursive Constructions of “Good Motherhood” in Infant Feeding Health Promotional Material in Ireland - Rodgers, Ornaith (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
This paper focuses on discursive constructions of “good motherhood” in discourses of infant feeding in contemporary health promotional material in Ireland. The study examines the multisemiotic composition of two pamphlets on breast and formula feeding, routinely given to mothers in Ireland after having a baby. These pamphlets are analysed using a model of multimodal critical discourse analysis (MCDA) in order to produce a comprehensive examination of the key discursive strategies and semiotic choices employed by the producers of these texts to influence parents’ decisions about infant feeding. The paper examines how mothers’ choices with regard to infant feeding are constrained by the positioning of breastfeeding as the optimal choice, and the discursive legitimisation of correlations between the practice of breastfeeding andthe ideal of good motherhood. It also highlights that these discursive strategies and semiotic choices are underpinned by discourses of attachment parenting, totalmotherhood and neoliberal risk culture. The paper argues that the health promotional texts which form the basis of this study, are part of a wider discourse of breastfeeding which is an ideologically infused moral discourse about what it means to be a good mother in an advanced capitalist society. It further concludes that the question of choice, which is central to so many women’s issues, is notably absent from the discourse of infant feeding, a factor that can have a strong negative impact on the wellbeing of new mothers.